2008
DOI: 10.1007/s11661-007-9462-5
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Radioscopic Visualization of the Solutal Convection during Solidification of a Ga-30 Wt Pct In Alloy

Abstract: Capabilities of the X-ray attenuation contrast radioscopy were used to provide a real-time diagnostic technique of the melt flow during unidirectional solidification of a Ga-30 wt pct In alloy from the bottom, which is significantly affected by solutal convection. The solidification process was visualized using a microfocus X-ray tube. The X-ray facility provided shadow radiographs at spatial resolutions of about 10 lm at frame repetition rates of 25 Hz. The optical flow approach was used to derive information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…horizontal beam and vertical sample [16,17]. Recent advances in compact microfocus X-ray source and detector technology have allowed solidification experiments, with spatiotemporal resolutions comparable to those reported in synchrotron-based studies, to be performed in home-laboratories [18,19] as well as under microgravity conditions on-board parabolic flights [20] and sounding rockets [21]. This article describes the results of extensive terrestrial-based near-isothermal in situ solidification experiments of Al-Ti-B inoculated and non-inoculated Al-Cu alloy samples using the XRMON-Gradient Furnace (GF) and associated X-ray diagnostics [21].…”
Section: Introductionmentioning
confidence: 99%
“…horizontal beam and vertical sample [16,17]. Recent advances in compact microfocus X-ray source and detector technology have allowed solidification experiments, with spatiotemporal resolutions comparable to those reported in synchrotron-based studies, to be performed in home-laboratories [18,19] as well as under microgravity conditions on-board parabolic flights [20] and sounding rockets [21]. This article describes the results of extensive terrestrial-based near-isothermal in situ solidification experiments of Al-Ti-B inoculated and non-inoculated Al-Cu alloy samples using the XRMON-Gradient Furnace (GF) and associated X-ray diagnostics [21].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, an increasing number of real-time X-ray imaging studies of solidification microstructures and phenomena in real metals have been reported, addressing a broad variety of topics such as dendritic growth, [20][21][22][23] coarsening, [24] morphological transitions, [23] dendrite fragmentation, [25][26][27] solute diffusion and convection, [22,28] and momentum transfer relations in eutectics [29] and monotectics. [30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanical destruction of the dendrites has to be considered as very unlikely, but a remelting of dendrite side arms may occur because of the redistribution of solute [10]. It is known that both the temperature profile and the solute concentration ahead of the solidification front are significantly modified by electromagnetically-driven convection [14,27]. A further important task of the melt flow consists in the transport of such fragments into undercooled regions adjacent to the solidification front [8], where a stimulation of nucleation and a free growth of equiaxed grains occur.…”
Section: Discussionmentioning
confidence: 99%